(untitled) (Global Journals of Research in Engineering, 2012)
Grinding is primarily a finishing operation where high temperature at the wheel-work interface adversely affects the physical properties of the ground surface in terms of induced surface and sub surface residual stress, surface roughness, micro cracks and dimensional deviation. Conventional application of cutting fluid often cannot control the high temperature generated especially during high speed grinding. Besides, environmental pollution, effect on human health and higher cost has been a great concern of researchers and industries. One of the possible solutions of such problems is the Minimum Quantity Lubricants (MQL) technique which has both economical and environmental advantages. The present investigation is to evaluate the influence of MQL on chip formation mode and surface roughness in grinding AISI 1045 steel with CBN wheel at different level of process parameters. The result indicated that, MQL enables the reduction in surface roughness and more favorable chip formation mode compared to dry grinding. The whole experiment has been repeated with Alumina wheel under same experimental conditions to assess the performance of CBN wheel. A Response Surface model has been developed to predict the surface roughness while grinding AISI 1045 steel with CBN wheel under MQL technique. The model is then checked and validated by comparing with experimental results and found reasonably accurate.